1990
DOI: 10.1557/proc-200-141
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Film Synthesis, Past and Present: A Select Review

Abstract: A review of the history of ferroelectric (FE) thin film synthesis is given covering the period of the 1960's to the present. Early methods, materials and applications are discussed. An assessment of the recent upsurge in activity takes note of current targeted applications, including nonvolatile memory, piezoelectric actuators, capacitors, and electro-optic devices. Focus is placed on similarities and differences in the most common film deposition processes. Comparison of microstructure and composition variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A variety of techniques, including radio-frequency (RF) magnetron sputtering [7,8], metal organic chemical vapour deposition (MOCVD) [9], pulsed laser deposition (PLD) [10] and solgel process [11,12], have been successfully used to prepare epitaxial, well-oriented and polycrystalline PLZT thin films. The optical properties such as photorefractivity, electrooptic effect, optical waveguides and optical storage in the PLZT thin films were also reported [11,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of techniques, including radio-frequency (RF) magnetron sputtering [7,8], metal organic chemical vapour deposition (MOCVD) [9], pulsed laser deposition (PLD) [10] and solgel process [11,12], have been successfully used to prepare epitaxial, well-oriented and polycrystalline PLZT thin films. The optical properties such as photorefractivity, electrooptic effect, optical waveguides and optical storage in the PLZT thin films were also reported [11,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Lead zirconate titanate (PZT) electroceramic thin films exhibit a wide variation in ferroelectric, piezoelectric and dielectric properties depending on the composition, microstructure and preparatory methods [1,2]. As a result these films have found numerous electronic applications [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many studies on the preparation of ferroelectric thin films via solution have been reported. 8,9 Very recently, we reported the preparation of YMnO 3 thin films by two types of solution method, a thermal decomposition method and a reflux method, and found that the reflux process drastically improved the reduction of firing temperature and the formation of dense microstructure. 10 The dielectric properties of the thin films must be closely associated with the microstructure of the films.…”
Section: Introductionmentioning
confidence: 99%